Monitored anesthesia care and asleep-awake-asleep techniques combined with multiple monitoring for resection of gliomas in eloquent brain areas: a retrospective analysis of 225 patients - San-Zhong Li; Ning Su; Shuang Wu; Xiao-Wei Fei; Xin He; Jiu-Xiang Zhang; Xiao-Hui Wang; Hao-Peng Zhang; Xiao-Guang Bai; Guang Cheng; Zhou Fei (Chinese Neurosurgical Journal, 2022)
Abstract Background Awake craniotomy (AC) has become gold standard in surgical resection of gliomas located in eloquent areas. The conscious sedation techniques in AC include both monitored anesthesia care (MAC) and asleep-awake-asleep (AAA). The choice of optimal anesthetic method depends on the preferences of the surgical team (mainly anesthesiologist and neurosurgeon). The aim of this study was to compare the difference in physiological and blood gas data, dosage of different drugs, the probability of switching to endotracheal intubation, and extent of tumor resection and dysfunction after operation between AAA and MAC anesthetic management for resection of gliomas in eloquent brain areas. Methods Two-hundred and twenty-five patients with super-tentorial tumor located in eloquent areas underwent AC from 2009 to 2021 in Xijing Hospital. Forty-one patients underwent AAA technique, and the rest one-hundred eighty-four patients underwent MAC technique. Anesthetic management, dosage of different drugs, intraoperative complications, postoperative outcomes, adverse events, extent of resection and motor, and sensory and language dysfunction after operation were compared between MAC and AAA. Result There was no significant difference in gender, KPS score, MMSE score, glioma grade, type, and growth site between the patients in the two groups, except the older age of patients in MAC group than that in AAA group. During the whole process of operation, there were greater pulse pressure difference (P = 0.046), shorter operation time (P = 0.039), less dosage of remifentanil (P = 0.000), more dosage of dexmedetomidine (P = 0.013), more use of antiemetics (81%, P = 0.0067), lower use of vasoactive agent (45.1%, P = 0.010), and lower probability of conversion to general anesthesia (GA, P = 0.027) in MAC group than that in AAA group. Blood gas analysis showed that PetCO2 (P = 0.000), Glu concentration (P = 0.000), and PaCO2 (P = 0.000) were higher, but SPO2 (P = 0.002) and PaO2 (P = 0.000) were lower in MAC group than that in AAA group. In the postoperative recovery stage, compared with that of AAA group, the probability of dysfunction in MAC group at 1, 3, 5, and 7 days after operation was lower, which were 27.8% vs 53.6% (P = 0.003), 31% vs 68.3% (P = 0.000), 28.8% vs 63.4% (P = 0.000), and 25.6% vs 58.5% (P = 0.000), respectively. Conclusion Compared with AAA, it seems that MAC has more advantages in the management for resection of gliomas in eloquent brain areas, and MAC combined with multiple monitoring such as cerebral cortical mapping, neuronavigation, and ultrasonic detection is worthy of popularization for the resection of gliomas in eloquent brain areas.